Anti-Angiogenic Agents in Management of Sarcoma Patients: Overview of Published Trials - Cren, Pierre-Yves; Lebellec, Loïc; Ryckewaert, Thomas; Penel, Nicolas (Frontiers in Oncology, 2020)
We reviewed all fully published clinical trials assessing anti-angiogenic agents in sarcoma patients (last issue 13 January 2020). Anti-angiogenic macromolecules (e.g. bevacizumab or ombrabulin) provide disappointing results. Many multikinase inhibitors have been assessed with non-randomized phase II trials with limited samples and without stratification according to histological subtypes, therefore interpretation of such trials is very challenging. On the contrary, pazopanib, regorafenib and sorafenib have been assessed using double-blind placebo-controlled randomized phase II or phase III trials. Compared to placebo, sorafenib demonstrates activity in desmoid-type fibromatosis patients. Based on results of phase 3 trial, pazopanib had obtained approval for treatment of pretreated non-adipocytic soft tissue sarcoma. Regorafenib is currently assessed in several clinical settings and provides significant improvement of progression-free survival in pre-treated non-adipocytic soft tissue sarcoma and in advanced pretreated osteosarcoma. Multikinase inhibitors is a breakthrough in sarcoma management. Many trials are ongoing. Nevertheless, predictive factors are still missing.